CONDITION AND TRENDS OF WALNUT PRODUCTION IN THE WORLD AND IN REPUBLIC OF SERBIA - Damir NAĐ; Zorica SREDOJEVIĆ; Danilo GAZDIĆ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Walnut is recognized by consumers as a healthy food with rich nutritional characteristics, which is widely used in the food and pharmaceutical industry. The aim of the research in this paper is to analyze the trend in the production of walnut in the period 2013-2022 observing world and Serbia. In this period the calculated base and chain indexes show a positive growth trend of the demand in the world for walnuts in shell and shelled. Production in Serbia has a negative trend, although the characteristics of the soil and climate and the needs of the market lead to the conclusion that there are all the necessary conditions for the participation of the production of this fruit species to have a much larger share in the agricultural production of Serbia. With the increase in the state's role in supporting producers of this stone fruit, benefits would be multiple, from employment of the workforce and increase in exports, to environmental protection and prevention of soil erosion.